(untitled) (Research, Society and Development, 2022)
Food allergy is often cited in dogs and humans, but in cats there are few reports that differentiate it from feline atopic skin syndrome, with similar symptoms. Itching of the face and neck in this species is frequently reported. The definitive diagnosis is made through the exclusion of other dermatological conditions and food tests. The elimination diet consists of removing some nutrient from the diet for a certain period and then performing challenges with the same food, with the aim of a cautious diagnosis. If the patient shows clinical signs during the challenge, he will be considered allergic to that food. Given the fact that we do not have well-defined criteria for this disease and the increase in the number of cases in the clinic, the present study aims to report the case of an no defined race feline that, after being treated without success for other skin diseases, showed improvement after treatment for allergy food.